Zero Trust Onboarding in HR Tech Safeguarding Applicant Tracking Systems against Deepfake Resumes and Credential Fraud - Diana Ussher-Eke,; UgoaghalamUche James,; Onum Friday Okoh, (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
The rapid evolution of artificial intelligence has introduced unprecedented challenges to human resources (HR) technology, particularly in safeguarding applicant tracking systems (ATS) from fraudulent activities. Among the most pressing threats are deepfake resumes and credential fraud, which exploit digital platforms to bypass traditional verification mechanisms and compromise organizational integrity. As hiring processes increasingly migrate to digital ecosystems, the risks associated with manipulated identities and fabricated qualifications demand robust, proactive security frameworks. Zero Trust, a security paradigm based on the principle of “never trust, always verify,” emerges as a critical solution for strengthening HR tech against these vulnerabilities. By embedding continuous identity validation, dynamic access controls, and risk-based authentication into the onboarding lifecycle, Zero Trust redefines how sensitive applicant data is protected and how legitimacy is ensured at every interaction point. This approach mitigates the potential for compromised talent pipelines, reputational damage, and financial losses stemming from fraudulent hiring decisions. Beyond technical resilience, Zero Trust fosters organizational trust, ensuring that recruitment processes remain transparent, secure, and aligned with ethical standards in talent acquisition. Ultimately, adopting Zero Trust in HR systems represents not only a safeguard against sophisticated cyber-enabled fraud but also a transformative step toward redefining digital trust in the future of work.
Keywords: Zero Trust Security; Human Resources Technology; Applicant Tracking Systems; Deepfake Resumes; Credential Fraud